2021
DOI: 10.1186/s12954-021-00537-w
|View full text |Cite
|
Sign up to set email alerts
|

A drug-related Good Samaritan Law and calling emergency medical services for drug overdoses in a Canadian setting

Abstract: Background People who use drugs (PWUD) are known to fear calling emergency medical services (EMS) for drug overdoses. In response, drug-related Good Samaritan Laws (GSLs) have been widely adopted in the USA and Canada to encourage bystanders to call emergency medical services (EMS) in the event of a drug overdose. However, the effect of GSLs on EMS-calling behaviours has been understudied. We sought to identify factors associated with EMS-calling, including the enactment of the Canadian GSL in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…Even so, GSDOA awareness and understanding alone fail to account for other contextual factors that may impact an individual’s willingness to call 9–1-1 and therefore should not be used as a proxy for GSDOA effectiveness. For example, research shows that one’s willingness to call 9–1-1 for an overdose may also depend on factors such as overdose setting (private vs. public) and previous experiences with EHS [ 24 , 81 , 82 ]. Lastly, there is no conclusive evidence about the effectiveness of Good Samaritan Laws, in part due to ongoing concerns around police presence in spite of these laws [ 34 , 36 , 82 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even so, GSDOA awareness and understanding alone fail to account for other contextual factors that may impact an individual’s willingness to call 9–1-1 and therefore should not be used as a proxy for GSDOA effectiveness. For example, research shows that one’s willingness to call 9–1-1 for an overdose may also depend on factors such as overdose setting (private vs. public) and previous experiences with EHS [ 24 , 81 , 82 ]. Lastly, there is no conclusive evidence about the effectiveness of Good Samaritan Laws, in part due to ongoing concerns around police presence in spite of these laws [ 34 , 36 , 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, research shows that one’s willingness to call 9–1-1 for an overdose may also depend on factors such as overdose setting (private vs. public) and previous experiences with EHS [ 24 , 81 , 82 ]. Lastly, there is no conclusive evidence about the effectiveness of Good Samaritan Laws, in part due to ongoing concerns around police presence in spite of these laws [ 34 , 36 , 82 ]. Police discretion and stigma can cause PWUD to be poorly treated by first responders at overdose events [ 34 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have assessed factors associated with calling 9-1-1 at an overdose among samples of people with variable knowledge of drug related Good Samaritan laws, which have been implemented in many states throughout the US [ 15 17 , 67 , 68 ]. Although our study included a substantial proportion of youth (aged 16–24), a population that has previously been identified as reticent to call 9-1-1 due to fear of criminalization and mistrust of police [ 6 , 23 , 69 , 70 ], we did not find that intent to call 9-1-1 differed by this age group (Block 1).…”
Section: Discussionmentioning
confidence: 99%
“…on the street) [ 15 , 16 , 28 ]. Additionally, a recent Vancouver study found lower odds of calling 9-1-1 among persons living in SROs compared to other private residences [ 68 ]. Bystanders to overdose in private residences may be concerned about lacking anonymity or losing housing as a result of drug use being discovered [ 91 , 92 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation